Hannah's heirs the quest for the genetic origins of Alzheimer's disease - Pollen, Daniel A. (Oxford Univ. Press, 1993)
Hannah's grandson charted his family's medical history over five generations and thereby provided priceless research in genetics. Pollen uses Hannah's illness as a starting point and a central story in his inside look at the medical detective story of the genetic origins of Alzheimer's disease.